A novel recycling approach for efficient extraction of titanium from high-titanium-bearing blast furnace slag. (1st February 2021) - Fan, Gangqiang; Wang, Meng; Dang, Jie; Zhang, Run; Lv, Zepeng; He, Wenchao; Lv, Xuewei
Highlights: A novel process for extraction titanium from high Ti-BF slag has been proposed. The effects of Fe2 O3, urea and sawdust additives on the reaction have been studied. The proposed novel recycling process has been assessed. The novel recycling process showed many potential advantages and great feasibility. Abstract: The recycling of high-titanium-bearing blast furnace slag (TiO2 > 23 wt.%) is an urgent problem that has attracted global research attention. To achieve high-efficiency, low-consumption, clean, and high value-added recycling utilization, a new process is proposed herein, which entails reacting a CH4 -H2 -N2 gas mixture with the titanium-bearing blast furnace slag to initially produce Ti(C, N, O) at a low temperature, whereafter the product is purified and chlorinated. The effects of Fe2 O3, urea, and sawdust on the reduction and carbonitriding characteristics are also investigated. The results indicate that the Fe2 O3 additive can promote the formation of Ti(C, N, O), while urea and sawdust are instrumental for enhancing gas diffusion in solid powders. The proposed novel recycling process was assessed and it evinced many advantages and great feasibility.